Connecting people and ideas from around the world: global innovation platforms for next‐generation ecology and beyond. Issue 4 (28th April 2015) - Jørgensen, Peter Søgaard; Barraquand, Frederic; Bonhomme, Vincent; Curran, Timothy J.; Cieraad, Ellen; Ezard, Thomas G.; Gherardi, Laureano A.; Hayes, R. Andrew; Poisot, Timothée; Salguero-Gómez, Roberto; DeSoto, Lucía; Swartz, Brian; et al.
Abstract : We present a case for using Global Community Innovation Platforms (GCIPs), an approach to improve innovation and knowledge exchange in international scientific communities through a common and open online infrastructure. We highlight the value of GCIPs by focusing on recent efforts targeting the ecological sciences, where GCIPs are of high relevance given the urgent need for interdisciplinary, geographical, and cross‐sector collaboration to cope with growing challenges to the environment as well as the scientific community itself. Amidst the emergence of new international institutions, organizations, and meetings, GCIPs provide a stable international infrastructure for rapid and long‐term coordination that can be accessed by any individual. This accessibility can be especially important for researchers early in their careers. Recent examples of early‐career GCIPs complement an array of existing options for early‐career scientists to improve skill sets, increase academic and social impact, and broaden career opportunities. We provide a number of examples of existing early‐career initiatives that incorporate elements from the GCIPs approach, and highlight an in‐depth case study from the ecological sciences: the International Network of Next‐Generation Ecologists (INNGE), initiated in 2010 with support from the International Association for Ecology and 20 member institutions from six continents.